9. a) x la 3 + x la 2 + x + 1 = x * x * x + x * x + x * 1 + 1 * 1 b) x la 3 + x la 2 - 4x - 4 = x * x * x + x * x - 4 * x - 4 * 1 c) x la 6 - x la 4 - 16x la 2 + 16 = x * x * x * x * x * x - x * x * x * x - [(16 * x) * (16 * x)] d) x la 5 + x la 3 - x la 2 - 1 = x * x * x * x * x + x * x * x - x * x - 1 * 1
10. a) x la 4 + 81 = x * x * x * x + 9 * 9 b) (x - 1) la 8 + (x - 1) la 4 = [(x - 1) * (x - 1) * (x - 1) * (x - 1) * (x - 1) * (x - 1) * (x - 1) * (x - 1)] + [(x - 1) * (x - 1) * (x - 1) * (x - 1)] c) 16 * (2x - 1) la 4 + 4(2x - 1) la 2 + 1 = 16 * [(2 * x - 1) * (2 * x - 1) * (2 * x - 1) * (2 * x - 1)] + 4 * [(2 * x - 1) * (2 * x - 1)] + 1 * 1.